PENGARUH KUALITAS PRODUK,CITRA MEREK,HARGA TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA PENGGUNA SEPEDA MOTOR MATIC YAMAHA MIODI KOTA PONTIANAK) - B31111003, Fery Marsuki (Jurnal Manajemen Update, 2016)
Competition in the business world is not a new thing for any marketer. The phenomenon where the market is filled with a variety of brands, with various promises manufacturers to meet the demands and desires of consumers. This requires marketers to put forward the brand as well as the experience of the brand to get priority purchasing decisions.Consumers today are very critical in selecting a product, the decision to buy a product greatly influenced by an assessment of product quality as well as the sacrifice or the price paid. Technological developments make motorcycle transportation is not longer a secondary requirement where the vehicle has become a necessity. Yamaha is a trademark that has been widely recognized by society, one of the featured products are favored, namely motor matic. Matic provides ease of use, especially for novice users of motor vehicles are bicycles, because the motor matic does not have to do the replacement gears manually. This study aimed to examine the effect of product quality, brand image and price of the purchasing decision matic Yamah Mio brand in Pontianak. This study, conducted by quantitative methods of causal form. In this study, conducted for distributing questionnaires to 100 users matic product brand Yamaha mio in Pontianak, using purposive sampling technique. After that, an analysis of the data obtained using quantitative data analysis. Quantitative analysis includes: Validity and reliability, Classical Assumption Test, Multiple Regression Analysis, hypothesis testing by testing thefeasibility of the model and t test, and analysis coefficient of determination (R2). Methode data processing using multiple regression analysis. The results show that: the quality of the product does not have a significant effect on purchasing decisions with regression coefficient of 0.336 while the significance value of 0.061 greater than 0.05 Î±, brand image positive and significant impact on the decision Purchases with a positive regression coefficient of 0.346 and the significance of 0.002 which is smaller than Î± of 0.05, the price does not significantly influence purchasing decisions with regression coefficient of 0.167 and a significance value of 0.315 greater than 0.05 Î±. Â  Keywords: Quality Product, Brand Image, Price, Purchase Decision Â